The Dual Role of Women Traditional Market Traders in Improving Family Economy in Sekkang Langnga Village, Pinrang Regency: The Dual Role of Women Traditional Market Traders in Improving Family Economy in Sekkang Langnga Village, Pinrang Regency - Sannawia (SOSIOLOGIA : Jurnal Agama dan Masyarakat, 2024)
This research aims to describe the economic conditions of the families of women traditional market traders in Sekkang Langnga Village, Pinrang Regency, as well as the strategies implemented by them to improve the family economy. Using qualitative descriptive methods, this research collects data through observation, in-depth interviews and documentation. The research results show that female traders not only function as household managers but also make a significant contribution to the family economy through trading activities in the market. Their role includes providing daily needs, children's education, and managing family health. The strategies implemented include saving, participating in social gatherings, and careful financial management, as well as utilizing social networks in the market for moral support and trading-related information. Support from family, especially husbands and children, as well as sharing household tasks with husbands, plays an important role in enabling them to carry out However, they face challenges such as income instability, heavy workloads, and lack of access to capital and training. However, this dual role provides economic stability and prosperity for the family, as well as improving women's social position in the community. This research highlights the importance of social support and policies that support gender equality to improve the economic conditions of women market traders. Support from the government and related institutions, in the form of adequate facilities, entrepreneurship training and access to capital, as well as increasing public awareness about gender equality, is needed to reduce the double burden that women often face. The conclusion of this research emphasizes that gender roles in society can change according to socio-economic conditions, and women traders have a significant contribution to the family economy.